Allopatric differentiation and morphometric growth in a Jamaican freshwater crab, with the discrimination of a cave phenotype - Stemmer, Manuel; Schubart, Christoph D. (Studies on neotropical fauna and environment, 2013)
The freshwater crab Sesarma fossarum inhabits surface and cave habitats in western central Jamaica (Cockpit Country). Comparisons among nine sampling sites across its distribution range revealed high intraspecific phenotypic diversity, including morphometric differences between populations from neighboring cave and surface habitats, which form part of the same river system. Specimens in two sampled caves show more slender walking legs and chelae than specimens from outside the caves. Overall, the morphometric results can help to determine onset of maturity and to understand morphological plasticity.